2018
DOI: 10.18203/2349-2902.isj20185121
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study comparing preservation of ilioinguinal nerve with neurectomy in open mesh repair of inguinal hernia

Abstract: Background: Postoperative pain after open mesh repair of inguinal hernia is an important challenge. Such type of pain sometimes does not respond to medical treatment including non-steroidal anti-inflammatory drugs and opiates. The objective of the present study was to evaluate the effect of preservation or division of the Ilioinguinal nerve on pain and post-operative symptoms, after open mesh repair of inguinal hernia.Methods: All patients undergoing surgery for tension free Lichtenstein mesh repair over a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…The difference in pain in the two groups was also statistically significant and the twotailed p value was 0.0184 (<0.05). 20 In the present study after one month follow up the pain after normal daily activities were present in 40% of patients in the neurectomy group (A) and 33.3% in the nerve preservation group (B). Pain during normal daily activities was noted in 11.1% in the neurectomy group and 24.4% in the nerve preservation group after 6 months follow up.…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…The difference in pain in the two groups was also statistically significant and the twotailed p value was 0.0184 (<0.05). 20 In the present study after one month follow up the pain after normal daily activities were present in 40% of patients in the neurectomy group (A) and 33.3% in the nerve preservation group (B). Pain during normal daily activities was noted in 11.1% in the neurectomy group and 24.4% in the nerve preservation group after 6 months follow up.…”
Section: Discussionsupporting
confidence: 42%
“…In the nerve preserved group 7, 5 and 2 patients had groin numbness at 7 days, 1 month, and 3 months, respectively with no statistically significant difference between both groups. 20 Mohanapriya reported that the incidence of post-operative numbness was higher in the neurectomy group at the 8 months follow-up. The incidence of hyperesthesia was high in both the study groups at 1 month follow up.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…For the remaining 31 studies, the full texts were obtained and reviewed. Sixteen studies were included [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], and 15 studies were excluded from the meta-analysis (three were not randomized [44][45][46], six RCTs performed a short follow-up [47][48][49][50][51][52], in three RCTs the timing of the follow-up was different from 6 and 12 months [53][54][55], two RCTs used the sutureless Trabucco technique [56,57], and one RCT analyzed the neurectomy of the iliohypogastric nerve [58]).…”
Section: Trial Identificationmentioning
confidence: 99%